Iodine binding to humic acid - Bowley, Hannah E.; Young, Scott D.; Ander, E. Louise; Crout, Neil J.M.; Watts, Michael J.; Bailey, Elizabeth H. (Elsevier, 2016)
The rate of reactions between humic acid (HA) and iodide (I-) and iodate (IO3-) have been investigated in suspensions spiked with 129I at concentrations of 22, 44 and 88 µg L-1 and stored at 10oC. Changes in the speciation of 129I-, 129IO3- and mixed (129I-+129IO3-) spikes were monitored over 77 days using liquid chromatography inductively coupled plasma mass spectrometry (LC-ICP-MS). In suspensions spiked with 129I- 25% of the added I- was transformed into organic iodine (Org-129I) within 77 days and there was no evidence of 129IO3- formation. By contrast, rapid loss of 129IO3- and increase in both 129I- and Org-129I was observed in 129IO3--spiked suspensions. However, the rate of Org-129I production was greater in mixed systems compared to 129IO3--spiked suspensions with the same total 129I concentration, possibly indicating IO3-—I- redox coupling. Size exclusion chromatography (SEC) demonstrated that Org-129I was present in both high and low molecular weight fractions of the HA although a slight preference to bond with the lower molecular weight fractions was observed indicating that, after 77 days, the spiked isotope had not fully mixed with the native 127I pool. Iodine transformations were modelled using first order rate equations and fitted rate coefficients determined. However, extrapolation of the model to 250 days indicated that a pseudo-steady state would be attained after ~ 200 days but that the proportion of 129I incorporated into HA was less than that of 127I indicating the presence of a recalcitrant pool of 127I that was unavailable for isotopic mixing.